MicroRNA-145-5p regulates the proliferation of epithelial ovarian cancer cells via targeting SMAD4 - Jie Zhou; Xiyi Zhang; Weiling Li; Yuanyuan Chen (BMC, 2020)
Abstract Background Epithelial ovarian cancer (EOC) is one of the most prevalent malignancies affecting females worldwide; however, its etiology mechanism remains unclear. In various malignancies, miR-145-5p is a widely accepted and versatile miRNA. Therefore, our research focused on exploring the activity and etiology of miR-145-5p in the modulation of metastasis, migration, and proliferation of EOC cells. The direct reactions between the 3'UTRs of SMAD4 mRNA and miR-145-5p were verified using dual luciferase reporter test. SKOV-3 cells were subsequently transfected using miR-145-5p mimics. Cell migration, death, and proliferation were evaluated using MTT, flow cytometry, and Transwell test. In addition, SMAD4 transcription and translation were evaluated using qRT-PCR and Western blot. Results We found that miR-145-5p expression was repressed prevalently in EOC tissues, apart from SMAD4 upregulation. Excessive miR-145-5p expression remarkably reinforced EOC cell death and repressed EOC cell proliferation. Furthermore, upregulated miR-145-5p expression noticeably repressed migration via MMP-2 and MMP-9 downregulation. Moreover, SMAD4 was downregulated via miR-145-5p transfection. The dual luciferase test revealed that miR-145-5p directly targeted SMAD4. Conclusions Our research suggests that miR-145-5p serves as a malignancy repressor and exerts an essential impact on inhibiting malignancy generation and reinforcing EOC death via targeting SMAD4. MiR-145-5p application could serve as a promising strategy to treat EOC.